Color Detection - Zeng, Ling-Wen; Cao, Shi-Lin (IntechOpen, 2020)
Chromogenic assays (color detection) result in colored reaction products. By detecting the color change before and after the reaction, substance concentration can be determined by the naked eye, light microscopes, or spectrophotometers. Color detection exhibits great potential in the field of quality monitoring, chemical technology, nanophysics, and clinical medicine, because of its rapid, direct, specific, convenient, and sensitive features. The intention of this book is to provide readers with a comprehensive overview of the principles, features, and applications of color detection.